A Schulman doubles masterbatch production capacity at Chinese plant. Issue 2 (February 2015) - Unknown
Abstract : Masterbatch manufacturer A. Schulman, Inc has commissioned a new production line at its facility in Dongguan, China, to accommodate increasing demand in its Masterbatch Solutions business. The plant's additional output will serve the needs of the packaging and personal care & hygiene industries in China, the company says.